Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1186/1472-6963-9-66
|View full text |Cite
|
Sign up to set email alerts
|

Patient-physician interaction in general practice and health inequalities in a multidisciplinary study: design, methods and feasibility in the French INTERMEDE study

Abstract: Background: The way in which patients and their doctors interact is a potentially important factor in optimal communication during consultations as well as treatment, compliance and follow-up care. The aim of this multidisciplinary study is to use both qualitative and quantitative methods to explore the 'black box' that is the interaction between the two parties during a general practice consultation, and to identify factors therein that may contribute to producing health inequalities. This paper outlines the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…This is in accordance with the general educational guidelines of what is generally considered as good doctor-patient communication: doctors need to be competent, have to know their job, while adopting a patient-centered style (Roter and Hall 2006). At the same time, this result contrasts with what physicians tend to do, namely using a more dominant communication style when dealing with patients from lower educational backgrounds (Verlinde et al 2012;Smith et al 2009;Kelly-Irving et al 2009). This means that doctors often adapt their communication style based only on ingrained prejudices, and therefore, in the opposite direction.…”
Section: Discussionmentioning
confidence: 80%
“…This is in accordance with the general educational guidelines of what is generally considered as good doctor-patient communication: doctors need to be competent, have to know their job, while adopting a patient-centered style (Roter and Hall 2006). At the same time, this result contrasts with what physicians tend to do, namely using a more dominant communication style when dealing with patients from lower educational backgrounds (Verlinde et al 2012;Smith et al 2009;Kelly-Irving et al 2009). This means that doctors often adapt their communication style based only on ingrained prejudices, and therefore, in the opposite direction.…”
Section: Discussionmentioning
confidence: 80%
“…Research has shown that communication, as an interactional process involving both doctors and patients, is key to understanding the quality of care patients receive [1,2,5-7,13]. Communicating and exchanging information are key to diagnosis and treatment [3,14-17].…”
Section: Introductionmentioning
confidence: 99%
“…It is based on a sequential exploratory design, in which each phase was conducted independently, on a different sample of patients and physicians (Figure 1; Kelly-Irving et al, 2009):…”
Section: Methodsmentioning
confidence: 99%